Can combined goal prioritization and implementation intentions promote adherence to the Mediterranean Diet? A randomized controlled trial - Miriam Capasso; Raffaele Pasquariello; Rosa Fabbricatore; Riccardo Vecchio; Mark Conner; Daniela Caso (Appetite, 2027)

Microbiome crosstalk and nutrition: the interplay between gut microbiota-organ axis and dietary factors - Menşure Nur Çelik; Merve Esra Çıtar Dazıroğlu; Büşra Atabilen Pınar; Maria Francesca Nanì; Barbara Romano; Duygu Ağagündüz; Raffaele Capasso (Food Research International, 2026)

Butyrate: A potential mediator of obesity and microbiome via different mechanisms of actions - Meryem Saban Güler; Sabriye Arslan; Duygu Ağagündüz; Ida Cerqua; Ester Pagano; Roberto Berni Canani; Raffaele Capasso (Food Research International, 2025)

A comprehensive review on food hydrocolloids as gut modulators in the food matrix and nutrition: The hydrocolloid-gut-health axis - Duygu Ağagündüz; Gizem Özata-Uyar; Betül Kocaadam-Bozkurt; Ayçıl Özturan-Şirin; Raffaele Capasso; Saphwan Al-Assaf; Fatih Özoğul (Food Hydrocolloids, 2023)

Probiotics, Live Biotherapeutic Products (LBPs), and Gut-Brain Axis Related Psychological Conditions: Implications for Research and Dietetics - Duygu Ağagündüz; Elif Çelik; Özge Cemali; Feray Gençer Bingöl; Çiler Özenir; Fatih Özoğul; Raffaele Capasso (Probiotics and Antimicrobial Proteins, 2023)

Hepatoprotective potential of selected medicinally important herbs: evidence from ethnomedicinal, toxicological and pharmacological evaluations - Mohammad Arman; Kazi Ashfak Ahmed Chowdhury; Md. Sazzadul Bari; Mohammad Forhad Khan; Maryam Md. Ataul Huq; Md. Areeful Haque; Raffaele Capasso (Phytochemistry Reviews, 2022)
Medicinal herbs are nature’s gift to humanity, contributing crucially to the preservation, maintenance and improvement of our health. In order to explore the hepatoprotective potential of prevalent medicinal plants, nine species were selected from different genera based on their ethnomedicinal records in treating different liver-related pathological conditions in South Asia. Besides, the available information was critically analyzed to gain new insights and directions for future investigations towards establishing such natural products as potent hepatoprotective agents or dietary supplements. The hepatoprotective activities of the species have been investigated in a wide variety of in vivo experimental models including carbon tetrachloride-, paracetamol-, iron-, mercuric chloride-, thioacetamide-, cyclophosphamide-, β- d -galactosamine-, cumene hydroperoxide-, α-naphthyl-isothiocyanate-, physical stress- and alcohol-induced hepatotoxicity in rats and mice. All the plants were consistent in their ability to possess hepatoprotective properties. As well, three bioactive isolates namely, schaftoside, echinocystic acid, and eclalbasaponin II were found to have promising hepatoprotective potential. However, extensive comparative studies are warranted in future to establish the relative hepatoprotective potentials of the nine species under discussion. Preparation of poly-herbal formulations from these plants and identification of hepatoprotective phytoconstituents from these plants might open up new avenues in the development of therapeutic hepatoprotective agents.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Biological activities of the essential oil from the leaves of Lantana montevidensis (Spreng) Briq. in mice - Maria Rayane Correia de Oliveira; Maria Gabriely de Lima Silva; Isabel Sousa Alcântara; Jaime Ribeiro Filho; Cícera Datiane de Morais Oliveira Tintino; Francisco Ernani Alves Magalhães; Anita Oliveira Brito Pereira Bezerr Martins; Renata Torres Pessoa; Antonia Eliene Duarte; José Galberto Martins da Costa; Sidney Gonçalo de Lima; Henrique Douglas Melo Coutinho; et al. (Environment, Development and Sustainability, 2021)

The Footprints of the Wreckage of the Italian Royal Navy Battleship Leonardo Da Vinci on the Mar Piccolo Sea-Bottom (Taranto, Southern Italy) - Giovanni Scardino; Francesco De Giosa; Marco D’Onghia; Pietro Demonte; Paola Fago; Gianluca Saccotelli; Eliana Valenzano; Massimo Moretti; Raffaele Velardo; Gennaro Capasso; Vera Corbelli; Giuseppe Mastronuzzi (Oceans, 2020)
Over the last two decades, the scientific interest for marine geophysical surveys has shown a huge increase, mostly for multidisciplinary applicability on different studies, from historical heritage to environmental remediation. One of the main research fields carried out through marine geophysical surveys is the study of the wreckage footprints connected to the seabed perturbation. In 2018, a strategic project planned by the Italian National Government Commissioner for the remediation in the Taranto area (Southern Italy) stands as a basic sample for such issues. The project aimed at the detection of anthropogenic impact in the highly polluted Mar Piccolo and Mar Grande basins seabed, through a multidisciplinary approach involving geological, biological, chemical, engineering, and ecological studies. The main purpose of the work was to identify any potential pollution source, focusing on anthropogenic sea-floor features such as uncontrolled dumping, wrecks, or other objects of peculiar origin. To achieve the purpose of the work, field surveys were planned and performed in order to direct a general policy and accurate planning for environmental remediation activities. Different marine geophysics methods were used to characterize the main sea-floor features and to detect each anthropogenic feature. A comparative analysis of a high-resolution dataset allowed to clarify the origin of some deep depressions on the Mar Piccolo sea-bottom, which at the first instance were associated with a natural origin, as the results of the Leonardo Da Vinci wreckage and related recovering activities. High-resolution morphobathymetric, magnetometric, and seismic data revealed the story of the Italian Royal Navy battleship which sunk on 2 August 1916 as a slight footprint on the Mar Piccolo seabed but a deep historical heritage of the city of Taranto. Moreover, final results demonstrate high-resolution marine survey methodologies’ complete applicability to environmental, historical, and scientific issues.

Mega-litter and remediation: the case of Mar Piccolo of Taranto (Ionian Sea) - Angelo Tursi; Vera Corbelli; Giulia Cipriano; Gennaro Capasso; Raffaele Velardo; Giovanni Chimienti (Rendiconti Lincei. Scienze Fisiche e Naturali, 2018)

Chemopreventive effect of the non-psychotropic phytocannabinoid cannabidiol on experimental colon cancer - Gabriella Aviello; Barbara Romano; Francesca Borrelli; Raffaele Capasso; Laura Gallo; Fabiana Piscitelli; Vincenzo Di Marzo; Angelo A. Izzo (Journal of Molecular Medicine, 2012)

Ultrapotent effects of salvinorin A, a hallucinogenic compound from Salvia divinorum, on LPS-stimulated murine macrophages and its anti-inflammatory action in vivo - Gabriella Aviello; Francesca Borrelli; Francesca Guida; Barbara Romano; Kevin Lewellyn; Maria De Chiaro; Livio Luongo; Jordan K Zjawiony; Sabatino Maione; Angelo A Izzo; Raffaele Capasso (Journal of Molecular Medicine, 2011)

Cannabidiol, a safe and non-psychotropic ingredient of the marijuana plant Cannabis sativa, is protective in a murine model of colitis - Francesca Borrelli; Gabriella Aviello; Barbara Romano; Pierangelo Orlando; Raffaele Capasso; Francesco Maiello; Federico Guadagno; Stefania Petrosino; Francesco Capasso; Vincenzo Di Marzo; Angelo A. Izzo (Journal of Molecular Medicine, 2009)

Inhibitory effect of the anorexic compound oleoylethanolamide on gastric emptying in control and overweight mice - Gabriella Aviello; Isabel Matias; Raffaele Capasso; Stefania Petrosino; Francesca Borrelli; Pierangelo Orlando; Barbara Romano; Francesco Capasso; Vincenzo Di Marzo; Angelo A. Izzo (Journal of Molecular Medicine, 2008)

Inhibitory effect of the herbal antidepressant St. John’s wort (Hypericum perforatum) on rat gastric motility - Raffaele Capasso; Francesca Borrelli; Gabriella Aviello; Francesco Capasso; Angelo A. Izzo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Increased endocannabinoid levels reduce the development of precancerous lesions in the mouse colon - Angelo A. Izzo; Gabriella Aviello; Stefania Petrosino; Pierangelo Orlando; Giovanni Marsicano; Beat Lutz; Francesca Borrelli; Raffaele Capasso; Santosh Nigam; Francesco Capasso; Vincenzo Di Marzo (Journal of Molecular Medicine, 2008)

Relaxant effect of capsazepine in the isolated rat ileum - Emilia Nocerino; Angelo Izzo; Francesca Borrelli; Francesco Capasso; Raffaele Capasso; Aldo Pinto; Lidia Sautebin; Nicola Mascolo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Cannabinoid CB 1 -mediated inhibition of stress-induced gastric ulcers in rats - Maria Paola Germanò; Valeria D'Angelo; Maria Rita Mondello; Simona Pergolizzi; Francesco Capasso; Raffaele Capasso; Angelo A. Izzo; Nicola Mascolo; Rita De Pasquale (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)